LEGAL PROTECTION FOR NOTARIES IN MAKING A DEED OF STATEMENT OF MEETING RESOLUTION (PKR) BASED ON CIRCULAR DECISIONS OUTSIDE THE GENERAL MEETING OF SHAREHOLDERS (GMS) MADE BY SHAREHOLDERS (Case Study at the Office of Notary Mulyani, S.H., M.Kn) - Vironika, Tiyas; Abas, Muhamad; Arafat, Zarisnov (Program Studi Hukum Fakultas Hukum Universitas Buana Perjuangan Karawang, 2024)
A notary is a public official authorized to make an authentic deed. The General Meeting of Shareholders (GMS) is an organ of a limited liability company that has the highest authority in the company that is not given to the Board of Directors and the Board of Commissioners. This study examines how circular decisions are made outside the GMS at PT WSA and how legal protection for notaries against the preparation of a deed of Meeting Decision Statement (PKR) based on Circular Decisions outside the GMS according to Law Number 2 of 2014 concerning Notary Positions. This study aims to find out the circular decision making outside the GMS at PT WSA and the legal protection for notaries against the preparation of a deed of Meeting Decision Statement (PKR) based on the Circular Decision outside the GMS according to Law Number 2 of 2014 concerning Notary Positions. The research method used is qualitative with a normative juridical approach. The hypothesis in this study is that the circular decision of PT WSA is carried out without being attended or carried out in the presence of a Notary. The notary does not play a role in making circular decisions of PT WSA, the notary only pours the contents of the circular decision into an authentic deed. So that the Notary cannot be prosecuted criminally or civilly, because in making the deed, the statement of the meeting decision has been in accordance with the content of the circular decision outside the GMS made by the shareholders of PT WSA without reducing, adding and changing its content